Monitoring occurrence and relative levels of rhizosphere microorganisms on Rockwool tomato crops across the 2012/2013 growing season - Scott, George (2014)
The tomato is the 8th most economically important agricultural product and the 4th most economically important crop in the world. The UK delivers the 3rd highest tomato yields globally. Such intensive production is due to the adoption of soilless growing techniques in greenhouses utilising assimilation lighting and heating along with the addition of CO2 to extend the growing season and maximise yield. Soilless growing systems reduce the abundance of soil-borne pathogens on the plant roots but may pose increase risk from water-borne pathogens such as the oomycetes. Government pressure to increase consumer safety and reduce environmental impact has led to a reduction in the use of chemical pesticides and an increase in fertigation solution recycling. This creates a situation in which disease risk may be increased and the methods by which you can control the disease are reduced. In this study the microbial populations, associated with the rhizosphere, were monitored via a small scale microarray. Crops grown on three contrasting fertigation systems pSSF (part slow sand filtration), SSF (slow sand filtration) and a run-to-waste (RTW) system were monitored every two weeks throughout the 2012-2013 growing season and two crops grown at a nursery utilising two physical treatments, heat and UV, were monitored at four points during the season. Finally, rapid in-house real-time diagnostic assays utilising loop mediated isothermal amplification (LAMP) were developed. A number of differences were observed from the pSSF, SSF and RTW systems. The RTW system exhibited lower taxa richness and species diversity with two significant differences in diversity observed between the pSSF-RTW and SSF RTWsystems. The RTW showed most taxa declining in abundance and persistence during the second half of the season. A general decline in taxa persistence was also observed in the second half of the season at the pSSF system but with reduced severity. The SSF system, however, showed an increase in taxa persistence during the second half of the growing season and also showed the highest persistence of oomycetes in the Pythium spp. Pythium spp. tended to persist later into the growing season, however, the pSSF and SSF showed Pythium spp. persistence 20 weeks earlier than the RTW. An increased number of fungal and oomycete pathogens were observed on the pSSF and SSF systems. There were more similarities than differences observed between the two crops grown on systems utilising physical treatments and both observed similar taxa richness and diversity. The remaining observations were apparent for all the crops monitored by microarray. A high number of possible fungal and oomycete pathogens were observed on all crops with taxa tending to be conserved between sites. Taxa observed at only a single site were generally saprophytic fungi. The Pythium spp. showed divergent patterns of persistence and abundance compared to all other taxa monitored in this study, with first occurrence mid-way through the season and general patterns of increasing abundance in the latter stages. Finally, LAMP assays developed for Pyrenochaeta lycopersici and Verticillium spp. targeting the ribosomal ITS region were shown to not be suitable for use. Two further assays developed targeting CDiT1 and SIX1, SIX3 and SIX4 from Pyrenochaeta lycopersici and Fusarium oxysporum f.sp lycopersici, respectively, were developed but not validated due to time constraints.